Domestic violence and its impact on members is a descriptive theoretical analytical study - Khalid, Dr. Ali Jaafar Khalid (Sulaimani Journal for Humanities, 2025)
Violence of all kinds at all levels in general and gender-based violence against women and children in particular is a widespread social phenomenon in all nations and societies, but varies in quantity and type from society to society Our society is loaded with their culture and other neighboring countries, we suffer from these violences, so at the international level in 1948, when the Universal Declaration of Human Rights was issued, several other resolutions were issued The Kurdistan Regional Government has issued the Law on Combating Domestic Violence No. 8 of 2011. It has also established special courts and directorates to investigate violence against women in all cities of the Kurdistan Region Gender gender is increasing in the Kurdistan Region. Domestic violence has many dimensions and factors, the most important of which is social culture, which is reflected in tribal customs, thought and patriarchal system, both of which were mixed with the power and political system of the country All of them affect the persistence and increase of domestic violence in general and violence against women in particular, although there is also the opposite violence, female violence against men within the family, which is the union of men Kurdistan publishes its statistics annually, but the amount and type of violence against women is much lower. This study is another scientific attempt to demonstrate the extent of violence in general and domestic violence and to determine the effects of violence on family members and society in general